2.5 billion beats! - F.Seling, Tenning; Wee, Cindy; Akir, Oriah; Wan Hassan, Sharifah Zakiah; Ramakrishnan, Prabha; Pereira, Helen; Ghazali, Azlina (Universiti Teknologi MARA, Sarawak, 2004)
Each day, a healthy heart beats one hundred thousand times and pumps 4,300 gallons of blood, or 1.5 million gallons a year. Without interruption, it accepts returned spent blood, depleted of oxygen and high in carbon dioxide. On the other hand, it blasts blood into the lungs for a rejuvenating boost of oxygen, takes it back and forces it out on the other side, back into circulation throughout the entire body. The single force of the heart's pumping action keeps the blood circulating through every tissue of the body, non-stop and throughout an entire lifetime.